Moving away from trading on the margins: Economic empowerment of informal businesses through FinTech. (18th July 2022) - Senyo, P. K.; Gozman, Daniel; Karanasios, Stan; Dacre, Nicholas; Baba, Melissa
Abstract: While there have been increasing studies on the impact of financial technology (FinTech), limited research has explored how FinTech supports economic empowerment for informal businesses. Drawing on institutional logics and a case study of mobile money—a FinTech innovation—this study develops a model of mobile money‐driven economic empowerment. We argue that this model is important to explain how those at the bottom of the economic pyramid, who are often neglected, use FinTech innovations to create and run informal businesses. Our findings and model explain the dynamics between logics, actors, and mobile money at three levels: regulatory, payments infrastructure, and informal economy. We identify three corresponding effects as outcomes of economic empowerment for informal businesses: greater access to start‐up capital, new employment opportunities, and improved financial management. By illustrating these effects, our study contributes to a better understanding of how FinTech innovations offer a possible pathway to economic empowerment for informal businesses.